THE IMPLEMENTATION OF THE OJIR APPLICATION AT CENTRAL WASTE BANK IN MALANG DISTRICT FOR THE MANAGEMENT OF HOUSEHOLD-SCALE ORGANIC WASTE DIVERSIFICATION PROCESSES - Nurhasan, Usman; Rohadi, Erfan; Nurindrasari, Diana; Arianto, Rakhmat; Pradibta, Hendra (LPPM Univ. Ibn Khaldun Bogor, 2023)
The Ojir application, a mobile-based innovation for organic waste management at Central Malang Waste Bank (BCM), provides an effective solution to streamline the collection and management of organic waste. Addressing environmental concerns such as food scraps, dry leaves, and fruits, the application responds to Ministry of Environment and Forestry (KLHK) data indicating that approximately 61.50% of total waste is organic, necessitating efficient management to reduce waste volume. Established in 2016, BCM faced challenges in manual data management and limited organic waste search capabilities. To address these issues, Ojir was introduced to modernize the organic waste management system. This innovation surpasses traditional waste management by incorporating a process of diversifying organic waste into maggot raw material. Beyond resolving existing waste bank issues, Ojir enhances management efficiency, allowing users to easily track and manage organic waste with increased accuracy. Consequently, the paradigm of organic waste management shifts towards modernity, effectiveness, and efficiency. Aligned with efforts to create a clean and sustainable environment, Ojir represents an innovative step in reinforcing the role of waste banks in handling organic waste in the technological era. The incorporation of the maggot raw material process further exemplifies the forward-thinking approach in sustainable waste management